Advances in Pretreatment of Straw Biomass for Sugar Production - Tan, Jinyu; Li, Yan; Tan, Xiang; Wu, Hongguo; Li, Hu; Yang, Song (Frontiers in Chemistry, 2021)
Straw biomass is an inexpensive, sustainable, and abundant renewable feedstock for the production of valuable chemicals and biofuels, which can surmount the main drawbacks such as greenhouse gas emission and environmental pollution, aroused from the consumption of fossil fuels. Although straw biomass is rich in organic content but is not sufficient for extensive applications because of its natural recalcitrance. Therefore, suitable pretreatment is a prerequisite for the efficient production of fermentable sugars by enzymatic hydrolysis. Here, we provide an overview of various pretreatment methods to effectively separate the major components such as hemicellulose, cellulose, and lignin, and enhance the accessibility and susceptibility of every single component. This review outlines the diverse approaches (e.g., chemical, physical, biological, and combined treatments) for the excellent conversion of straw biomass to fermentable sugars, summarizes the benefits and drawbacks of each pretreatment method, and proposes some investigation prospects for the future pretreatments.